Effects of piezoelectric actuatioin on delamination in transversely loaded composite plates - Nazwan bin Ghazali (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
Composite materials are known for their special characteristics which include its superior strength, good fatigue performance and weight reduction. However, composite materials have much more complex impact performance compared to conventional metallic materials. In fact, composite materials tolerate poorly to the impact loads as a number of different failure modes may occur, namely, matrix cracks, fiber fracture and delamination. Delamination plays as a degradation factor of the composite plate's stiffness when subjected to the low velocity impact loading. Consequently, there are various methods that have been used to improve the damage tolerance within laminates in composite plates. This present work reports the possibilities of using piezoelectric materials to reduce delamination in composite plates subjected to low velocity impact. For the purpose of this investigation the piezoelectric-host mathematical model for curvature was formulated and validated with the simulation approximation from the literature. The equations then were derived for different configurations to search for the maximum curvature which could be produced by piezoelectric actuator. LS-DYNA was utilized to simulate the model for the purpose of curvature validation and sets of different impact models were also constructed. Therefore, the configuration of top and bottom unimorph piezoelectric-host plate is selected as it gives the highest curvature. The delamination was modeled using a tiebreak based damage model and validated with the work in literature. Various configurations regarding the piezoelectric-composite model in terms of the placement of actuators, different size of actuators and variation of piezoelectric voltages were then implemented to study the effects of piezoelectric actuation on a plate when subjected to low energy impact loads. The top and bottom unimorph piezoelectric actuators were able to increase the plate's bending stiffness and reduced the resultant load which then decreased the interlaminar stresses acting within the laminates. Also, using this configuration, the piezoelectric actuators which cover the whole top and bottom surfaces of composite plate and the optimum value of voltage applied were proven to reduce and prevented delamination within the composite laminates.